Identifying support needs for people with intellectual disability and their families through a family quality of life survey in Kenya - Wanjagua, Rachael Wachera (Department of Health and Rehabilitation Sciences, 2019)
Intellectual disability (ID) is associated with limitations in cognitive, practical and adaptive functions. Individualised supports therefore enhance functioning for people with ID. Families often manage supports for their ID members alone. If not supported, the family quality of life (FQOL) is affected, which also affects the quality of life of the disabled member. FQOL therefore is an outcome measure for support services and strategies. In Kenya, FQOL and supports of families with individuals with ID is not known. This study’s purpose was to understand the FQOL of people with ID and their families and their support needs. The methodology used was a qualitative design, exploring perceptions of 7 people with mild ID and 8 caregivers on FQOL and support needs through interviews and 2 focus group discussions (FGDs). The Beach Centre Family Quality of Life Conversation Guide was used and piloted with 2 people with ID and 2 caregivers. It was adapted by simplifying the questions for people with ID and translated into Swahili. The study had emancipatory approaches with 2 people with ID and 1 caregiver as research assistants. 10 participants were identified through special schools and a village elder from each zone namely Nyahururu, Kinamba, Ol’ngarua and Mailoinya in Laikipia County. 2 participants for each category were selected through random sampling. Informed consent was received from all participants and caregivers of people with ID. Ethical approval was granted by the Human Research Ethics Committee of the University of Cape Town and a research permit granted by the Kenya National Commission of Science, Technology and Innovation. Data was collected and recorded on a mobile device. Identification codes were used to protect anonymity. Verbatim data was transcribed and checked by participants in FGDs. Confirmed data was translated into English and deductive and inductive analysis was done using Dedoose version 7.5.15. Similar data from the 5 domains in the Beach Centre FQOL Conversation Guide was coded together to develop the theme (community supports). FindingsFQOL in Kenya can be described through family interaction, parenting, emotional wellbeing, disability-related supports, physical/material wellbeing and community supports. Poverty, rights of people with ID and cultural constructions of disability can inform disability-related services, government policies and guidelines. Study limitations: The findings are representative of support needs for families of people with mild ID. The study gathered perspectives of people with ID and caregivers, and hence more views could be gathered from other family members. This study was conducted in rural settings and should be interpreted with this in mind.